The dog in the diamond collar - Lisle, Rebecca (Andersen Press, 2006)
Is Clinky Monkey, a dog with a diamond-studded collar, connected to the kidnapping of young Timothy Potts-Smythe? In trying to solve this mystery three young boys have encounters with bears, a boy and a big gorilla
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Bruder; Detektiv; Kindesentziehung; Vermisstes Kind; Children of the rich / Crimes against / Juvenile fiction; Kidnapping / Juvenile fiction; Missing persons / Investigation / Juvenile fiction; Children's humourous stories / Fiction; Kidnapping; Missing persons / Investigation; Children's stories; Humorous fiction; Children's fiction; Fiction; Juvenile works; Kinderbuch; Humoristische Darstellung